Spatial disparities and multilevel determinants of childhood diarrhea in Mozambique: Evidence from the 2022–2023 Demographic and Health Survey (DHS) - Thomas Kidanemariam Yewodiaw; Mihret Getnet; Mequanent Dessie Bitewa; Hiwot Tezera Endale (PLoS ONE, 2026)
Background Childhood diarrhea remains a major public health problem, particularly in sub-Saharan Africa, contributing substantially to morbidity and mortality and hindering progress toward Sustainable Development Goal 3 (SDG 3), which aims to end preventable under-five deaths. Marked regional variations in diarrhea burden highlight the need for updated analyses to guide public health planning and resource allocation. This study examines the spatial distribution and key determinants of diarrhea among under-five children to inform targeted interventions. Methods Data from 9,799 under-five children in the 2022–2023 Mozambique Demographic and Health Survey were analyzed to estimate diarrhea prevalence and identify associated determinants. Weighted analysis, spatial scan statistics (SaTScan), hotspot mapping, and multilevel logistic regression were used to assess individual- and community-level factors. Significant predictors were identified using adjusted odds ratios (AORs) with 95% confidence intervals (CIs) and p ≤ 0.05. Model variation was assessed using the intra-class correlation coefficient (ICC), median odds ratio (MOR), and proportional change in variance (PCV), and spatial patterns were mapped using ArcGIS. Results The weighted prevalence of diarrhea among under-five children in Mozambique was 8.8% (95% CI: 7.8–9.6%), highest in Niassa (14.5%), Cabo Delgado (14.0%), and Maputo City (13.4%), and lowest in Maputo Province (5.1%), Zambézia (5.5%), and Manica (5.8%). Multilevel analysis showed that children aged 12–23 months had higher odds of diarrhea (AOR = 1.36, 95% CI: 1.11–1.66). In contrast, children aged 24–59 months (AOR = 0.49, 95% CI: 0.41–0.59), maternal education (AOR = 0.77, 95% CI: 0.63–0.96), and rural residence (AOR = 0.69, 95% CI: 0.52–0.91) were associated with lower odds. Children residing in Nampula, Zambézia, Manica, Sofala, and Maputo Province had significantly lower odds of diarrhea compared to those in Niassa. Health-seeking behavior was strongly associated with reported diarrhea (AOR = 4.85, 95% CI: 4.10–5.74), possibly reflecting reporting bias. Conclusions Childhood diarrhea in Mozambique exhibits marked regional variation, with the highest burden in Niassa, Cabo Delgado, and Maputo City, and the lowest in Maputo Province, Zambézia, and Manica. Key determinants include child age, maternal education, and geographic region, while rural residence appears protective. These findings highlight the need for targeted, age- and region-specific interventions and strengthened maternal and community support to reduce childhood diarrhea and accelerate progress toward SDG 3.